The determinants of Waqf sustainability in Malaysia: A PLS-SEM analysis - Noraina Mazuin, Sapuan; Nur Azni, Mohd Zeni (Universiti Malaysia Sarawak, 2021)
Over the years, Waqf institutions has played an important role in addressing range of socio-economic development of ummah in the world. Waqf has been growing with time and there are increasing expectation surroundings the role of Waqf institutions. Nevertheless, lately the performance of Waqf institutions in Malaysia have cope with issues of inefficiency. According to the literature, inefficiency of Waqf performance is associated with internal factor which is Waqf management. Due to the matter, researchers agreed that Waqf institutions is in need of a holistic Waqf management reform to solve the arise issues. Following the issue, this study investigates the effect of efficient Waqf management determinants on the sustainability of Waqf institutions for long term growth in Malaysia. This study used a quantitative research methodology and a selected sample of 99 respondents in Waqf institutions were analyzed. The results were examined using partial least squares-structured equation modelling (PLS-SEM). This study empirically reveals that the determinants of efficient Waqf management positively influence the sustainability of Waqf institutions for long term growth. The result of this study will enhance the understanding of existing conceptual literature on the important of comprehensive Waqf management determinants in influencing the sustainability of Waqf institutions in Malaysia.